Growth and yield estimation of Chamaecyparis spp. through tree ring analysis - Kharal, D. K.; Fujiwara, T. (Banko Janakari, 2013)
Tree ring analysis is one of the most useful methods in volume and biomass estimation especially of the conifer trees. Ring width and ring density are important parameters in dendrochronological research. The present research was carried out with the aim of estimating the radial and volumetric growth of the Japanese Cypress trees (Chamaecyperis obstusa and C. pisifera). Destructive method was used while collecting the wood samples from the selected trees. Ring width and ring density were measured using soft X-ray densitometry method using micro-densitometer. Computer programme, developed by the Forestry and Forest Products Research Institute, Japan was used to analyze the ring with and ring density data. The average ring width of the Chamaecyparis spp. was found to be about 3.4 mm at the age of 30 years. However, two types of growth pattern were observed in the trees. Average radial growth was about 5% every year during the first 20 years of the tree age, whereas, the average radial growth was negative during the age of 20–30 years. Average density of the tree rings were increased by about 11% in each height of the trees starting from the ground. Similarly, the stem density decreased by about 3.4% annually along the radial direction from the pith. DOI: http://dx.doi.org/10.3126/banko.v22i2.9197 Banko Janakari: A Journal of Forestry Information for Nepal Vol. 22, No. 2, 2012 November Page: 36-42 Uploaded date: 12/1/2013